Matrix metalloproteinase-9 as an independent predictor of recurrence after catheter ablation of atrial fibrillation - Goryachiy, A. V.; Gozhenko, A. I.; Levchenko, E. M.; Goriachyi, V. V.; Kuznetsova, M. A.; Arapu, M. I. (Journal of Education, Health and Sport, 2017)
Objectives: In this study, the serum level of matrix metalloproteinase-9 was studied as an independent predictor of recurrence after catheter ablation of a persistent form of atrial fibrillation.Methods: The study included 46 patients with a persistent form of atrial fibrillation. In all patients, serum level of matrix metalloproteinase-9 was measured before the procedure of catheter radiofrequency ablation and its association with recurrence of arrhythmia at the end of the postoperative period was estimated.Results: The follow-up period was 12.3+ for 6.4 months, in 16 (34.7%) patients there was a relapse of arrhythmia after the procedure of catheter radiofrequency ablation. The baseline level of matrix metalloproteinase-9 was higher in patients with relapsed arrhythmia (297.73 + 81.28 and 234.41 + 93.36 ng / ml, respectively, p=0.006). Multivariate analysis showed that parameters such as the level of matrix metalloproteinase-9, the history of atrial fibrillation and the diameter of the left atrium were independent predictors of arrhythmia recurrence.Conclusion: The serum level of matrix metalloproteinase-9 is an independent predictor of arrhythmia recurrence after performing the procedure of catheter radiofrequency ablation in patients with persistent form of atrial fibrillation.